57x=-15

Multiply both sides of the equation by 75.

75⋅57⋅x=75⋅-15

Simplify 75⋅57⋅x.

Cancel the common factor of 7.

Cancel the common factor.

75⋅57⋅x=75⋅-15

Rewrite the expression.

15⋅5⋅x=75⋅-15

15⋅5⋅x=75⋅-15

Cancel the common factor of 5.

Cancel the common factor.

15⋅5⋅x=75⋅-15

Rewrite the expression.

1⋅x=75⋅-15

1⋅x=75⋅-15

Multiply x by 1.

x=75⋅-15

x=75⋅-15

Simplify 75⋅-15.

Cancel the common factor of 5.

Factor 5 out of -15.

x=75⋅(5(-3))

Cancel the common factor.

x=75⋅(5⋅-3)

Rewrite the expression.

x=7⋅-3

x=7⋅-3

Multiply 7 by -3.

x=-21

x=-21

x=-21

Solve for x 5/7x=-15